Factor affecting local commercial bank performance: case of six local commercial banks in Malaysia / Nadia Nasir - Nasir, Nadia (2018)
This paper is to examine the factors that affecting local commercial bank performance in Malaysia that extracted for sixteen years from 2001 to 2016. The objective of this study is to determine the relationship between gross domestic product (GDP), bank size, liquidity and deposit of local commercial bank in Malaysia. It is also to examine the most significant that affects local commercial bank performance in Malaysia. This paper employs Pooled Ordinary Least Square Method (POLS) in Oder to get the best result. The result shows that only three variables which are Gross Domestic Product (GDP) bank size and deposit have significant relationship. Furthermore, another one variable which is liquidity have insignificant relationship with local commercial bank performance in Malaysia.